Answer:
B
Step-by-step explanation:
Answer:
x=13
Step-by-step explanation:
9^2 * 27^3 = 3^x
We need to get each term with a base of 3
9^2 = (3^2) ^2
We know that a^b^c = a^(b*c)
(3^2) ^2 = 3^(2+2) = 3^4
27^3 = (3^3) ^3 = 3^(3*3) = 3^9
Replacing these in the original equation
3^4 * 3^9 = 3^x
We know that a^b *a^c = a^(b+c)
3^4 * 3^9 =3^(4+9) = 3^13 = 3^x
The bases are the same, so the exponents must be the same
x=13
Answer:
Step-by-step explanation:
Yes
Answer:
The answer of 2 x 3 would be 6
Step-by-step explanation:
The reason why 2 x 3 or 2 times 3 would be six/6. Is because if you had 2 pairs of 3 items, you would get a total of 6 items. And if you had 3 pairs of 2 items, you would still have a total of 6 items.